Exploring the paths between self-compassionate attributes and actions, body compassion and disordered eating - Barreto, Margarida de Carvalho Teixeira (2018)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação